Evidence for genetic predisposition to desmoid tumours in familial adenomatous polyposis independent of the germline APC mutation. Issue 12 (11th November 2004) - Sturt, N J H; Gallagher, M C; Bassett, P; Philp, C R; Neale, K F; Tomlinson, I P M; Silver, A R J; Phillips, R K S
Abstract : Background: Many patients with familial adenomatous polyposis (FAP) die from desmoid tumours which can arise spontaneously but often appear to be surgically induced by prophylactic colectomy. FAP results from germline adenomatous polyposis coli ( APC ) gene mutations and desmoids arise following biallelic APC mutation, with one change usually occurring distal to the second β-catenin binding/degradation repeat of the gene (3′ to codon 1399). We have suggested that because families with germline mutations in this region already have the requisite change, they are more likely to develop desmoids. However, there are families with 5′ germline mutations where desmoids are common. Patients and methods: We examined desmoid risk dependent on germline APC mutation, sex, history of abdominal surgery, and family history in FAP patients from the St Mark's Hospital Polyposis Registry. Results: Overall desmoid prevalence was 15%. Desmoids tended to cluster in susceptible individuals, irrespective of the germline APC mutation. Independent predictors of increased desmoid risk were: germline mutation distal to codon 1399; any family history of disease; and a strong family history of desmoids. A family history of multiple desmoids (>1) increased an individual's own risk of multiplicity. Females had twice the odds of developing desmoids compared with males. There was no significant interaction between any of the three explanatory variables. Conclusions: Our results indicate the influence of unknown genetic factors independent of APC in susceptibility to desmoid tumours in FAP. The data have implications in terms of clinical management of FAP patients and assessing the balance between chemoprevention and prophylactic colectomy.